Improving Arm Muscle Strength Through the Application of the STAD Cooperative Learning Model in Students in Grades X-3 of SMA Negeri 1 Banjarbaru - Fitriani, Ika Nur; Indah, Eka Purnama; Sani, Abdullah (Empiricism Journal, 2026)
This study aimed to improve the arm muscle strength of students in Class X-3 at SMA Negeri 1 Banjarbaru through push-up training implemented using the Student Teams Achievement Division (STAD) cooperative learning model supported by audiovisual media. Although STAD and audiovisual media have frequently been used to enhance student engagement, limited classroom action research has examined their combined application with progressively varied push-up exercises in senior high school physical education. The study employed a classroom action research design conducted in two cycles and involved 35 students during the second semester of the 2025/2026 academic year. Data were collected through observation, a 60-second push-up performance test, and documentation. During the pre-cycle stage, students completed the exercises without instructional intervention. In Cycle I, the intervention incorporated the STAD model, audiovisual demonstrations, and several push-up variations. In Cycle II, the number of repetitions for each exercise was increased progressively. The results showed that classical mastery improved from 31% in the pre-cycle stage, involving 11 students, to 54% in Cycle I, involving 19 students, and further increased to 86% in Cycle II, involving 30 students. Correspondingly, the proportion of students who had not achieved mastery decreased from 69% to 46% and then to 14%. These findings indicate that STAD-based cooperative learning, supported by audiovisual media and progressive repetition, contributed to improved arm muscle performance in the observed classroom context.